2021
DOI: 10.3390/molecules27010060
|View full text |Cite
|
Sign up to set email alerts
|

Plant Protein-Based Delivery Systems: An Emerging Approach for Increasing the Efficacy of Lipophilic Bioactive Compounds

Abstract: The development of plant protein-based delivery systems to protect and control lipophilic bioactive compound delivery (such as vitamins, polyphenols, carotenoids, polyunsaturated fatty acids) has increased interest in food, nutraceutical, and pharmaceutical fields. The quite significant ascension of plant proteins from legumes, oil/edible seeds, nuts, tuber, and cereals is motivated by their eco-friendly, sustainable, and healthy profile compared with other sources. However, many challenges need to be overcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 209 publications
(213 reference statements)
0
23
0
Order By: Relevance
“…Another approach is based on modifying the characteristics of lipid-based carriers, such as liposomes, by grafting polymers, generally poly(ethylene glycol) (PEG), onto the surface to avoid their rapid uptake by mononuclear cells and, therefore, rapid clearance [ 185 ]. Furthermore, protein modification has been reported to improve their performance as delivery systems: physical treatments, such as irradiation, heating, and high-pressure treatments, or chemical treatments, such as glycation, phosphorylation, acylation, deamidation, and cationization, succeeded in eliminating some of their constituents or adding functional groups, thereby improving the characteristics of proteins and making them more suitable for use as carriers [ 186 ]. Finally, the use of potentially toxic crosslinking agents such as formaldehyde and glutaraldehyde in the production of microcapsules by coacervation can be overcome by using natural crosslinkers, such as genipin, citric acid, and tannic acid [ 187 ].…”
Section: Challenges Of and Limitations To The Use Of Biopolymeric And...mentioning
confidence: 99%
“…Another approach is based on modifying the characteristics of lipid-based carriers, such as liposomes, by grafting polymers, generally poly(ethylene glycol) (PEG), onto the surface to avoid their rapid uptake by mononuclear cells and, therefore, rapid clearance [ 185 ]. Furthermore, protein modification has been reported to improve their performance as delivery systems: physical treatments, such as irradiation, heating, and high-pressure treatments, or chemical treatments, such as glycation, phosphorylation, acylation, deamidation, and cationization, succeeded in eliminating some of their constituents or adding functional groups, thereby improving the characteristics of proteins and making them more suitable for use as carriers [ 186 ]. Finally, the use of potentially toxic crosslinking agents such as formaldehyde and glutaraldehyde in the production of microcapsules by coacervation can be overcome by using natural crosslinkers, such as genipin, citric acid, and tannic acid [ 187 ].…”
Section: Challenges Of and Limitations To The Use Of Biopolymeric And...mentioning
confidence: 99%
“…They are biocompatible, biodegradable, non-toxic, and stable. Due to their hydrophobic nature and low solubility in aqueous solutions, they provide protection and controlled release of the loaded drugs [ 56 , 185 , 186 , 187 ]. Gliadin nanoparticles are suitable nanocarriers for various hydrophilic therapeutic agents [ 188 ].…”
Section: Plant-based Biopolymeric Nanoparticles Used For Healthcare A...mentioning
confidence: 99%
“…The rise of plant milk, artificial meat, and plant yogurt, among others, further confirms this point. Additionally, recent studies have found that plant proteins may be more suitable than traditional animal proteins to develop into delivery vectors for bioactive substances [ 23 , 24 ]. For example, zein and gliadin can produce carriers that continuously release active substances, avoiding the use of toxic chemical crosslinkers and opening up new directions for the application of active substances in food systems [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%